Family-based intervention for child and adolescent mental health : a core competencies approach - Allen, Jennifer L.; Hawes, David J.; Essau, Cecilia A. (Cambridge : Cambridge University Press, 2021)
The most effective treatments for child and adolescent psychopathology are often family-based, emphasising the active involvement of family members beyond the referred individual. This book details the clinical skills, knowledge, and attitudes that form the core competencies for the delivery of evidence-based family interventions for a range of mental health problems. Offering practical case studies to illustrate treatment principles, and discussing barriers to treatment and problem-solving in relation to common difficulties. Covers topics such as anxiety, attention-deficit hyperactivity disorder, sleep, and eating disorders. Therapist competencies are thoroughly examined, from the role they play in severe/complex cases and in achieving successful outcomes to commonly misunderstood aspects of family-based interventions and how they can be enhanced. Clinical approaches to working with diverse families, and those of children affected by parental psychopathology, child maltreatment and family violence are also explored. Essential reading for psychologists, psychiatrists, paediatricians, mental health nurses, counsellors and social workers.
Title from publisher's bibliographic system (viewed on 02 Mar 2021).
Keywords: Child psychopathology -- Treatment; Adolescent psychopathology -- Treatment; Family psychotherapy